7x-36=6x+3

Simple and best practice solution for 7x-36=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-36=6x+3 equation:


Simplifying
7x + -36 = 6x + 3

Reorder the terms:
-36 + 7x = 6x + 3

Reorder the terms:
-36 + 7x = 3 + 6x

Solving
-36 + 7x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-36 + 7x + -6x = 3 + 6x + -6x

Combine like terms: 7x + -6x = 1x
-36 + 1x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
-36 + 1x = 3 + 0
-36 + 1x = 3

Add '36' to each side of the equation.
-36 + 36 + 1x = 3 + 36

Combine like terms: -36 + 36 = 0
0 + 1x = 3 + 36
1x = 3 + 36

Combine like terms: 3 + 36 = 39
1x = 39

Divide each side by '1'.
x = 39

Simplifying
x = 39

See similar equations:

| 6y+6=18 | | -16x^2+80x=100 | | -4x+9=-39 | | b/1+6=2 | | -x+6=-21+8x | | u=3(5-u)+1 | | 4+6x=-62 | | 3(3x-4)=2x-8 | | 4t+3(2-t)=13 | | 2+7x=-5 | | -6(3x+6)+2= | | 3x+4=-5+2x | | -7x-8=-71 | | -7-2x=-9 | | (2t^2-t-6)(2t^2+2t-1)= | | 7(2y-3)=-16 | | -5+4x=35 | | 40+35=b | | 5n+8n= | | 64=-16x^2+80x | | 3-p-4+p= | | 3(4x+12)=48 | | 45+35c=b | | 1-5a+a-8= | | 1607-1531= | | 118=-16x^2+80x | | 5q-6=2(q+3) | | v+4v= | | -1(x-4)+2=6(x+3) | | 4x+11x=-2 | | 6+3x=-15-4x | | m-4-6m= |

Equations solver categories